In situ growth of mycelium in a lignocellulosic scaffold enabled by cellulose nanofibrils for lightweight insulation - Hajam, Maryam El; Sun, Wenjing; Hafez, Islam; Howell, Caitlin; Tajvidi, Mehdi (Elsevier, 2025)
Mycelium-lignocellulosic fiber composites (MLFCs) offer a promising sustainable alternative to lightweight, petroleum-based materials and are gaining significant interest across various sectors. However, creating low-density MLFCs that provide superior thermal and sound insulation properties along with good mechanical strength remains a substantial challenge. In-mold packing is the primary fabrication process explored so far for MLFCs, limiting the ability to design complex shapes, and expanding potential applications. Growing mycelium on pre-produced low-density lignocellulosic foam scaffold substrates is an innovative process that represents a promising, yet underexplored, approach for MLFCs. This approach offers the potential for design flexibility and enhanced structural properties. In this study, hybrid low-density foams made from lignocellulosic fibers, cellulose nanofibrils (CNFs), and mycelium (Trametes versicolor) were developed and assessed as foam-like insulation materials. A foam-forming method enabled by a surfactant was used to prepare low-density foam scaffold substrates from hardwood and softwood fibers with CNFs as a binder. The raw scaffold substrates and the final MLFCs were characterized for thermal conductivity, sound absorption, water resistance, mechanical strength, and morphological properties. The composites demonstrated excellent thermal insulation, soundproofing, and mechanical strength, as well as thermal and sound properties comparable to or even better than expanded polystyrene (sound absorption coefficient > 0.9 at 1600 Hz). Overall, the results showed that MLFCs have strong potential for further exploration in semi-structural applications, such as lightweight insulating infill panels and protective packaging, offering environmentally friendly and resource-efficient solutions for the construction insulation and packaging markets.
Keywords: 40 Engineering; 4016 Materials Engineering; Materials; 4016 Materials engineering; 4017 Mechanical engineering